A nanomembrane for adsorbing trace residual ions and a preparation method and application thereof

CN122999160APending Publication Date: 2026-10-30YUNNAN THREE CIRCLES SINOCHEM FERTILIZERS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611495862.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

该装置运行不足三个月即出现换热器温差下降15%以上、填料布水不均、喷嘴堵塞,清洗频次从每年两次增至每季度一次,每次化学清洗消耗大量柠檬酸与缓蚀剂,伴随48h以上停车损失

Benefits of technology

1.本申请的多孔吸附层中含有铈的氢氧化物纳米颗粒,该颗粒可与磷酸根发生配位作用,将痕量磷酸根固定于多孔吸附层孔壁表面。壳聚糖链上的羟基和氨基可与钙离子发生配位络合,将钙离子固定于多孔吸附层孔壁表面。聚乙烯亚胺与壳聚糖经戊二醛交联后形成三维互穿网络,增强多孔吸附层的机械强度并调节孔道结构,使痕量钙离子可快速扩散至壳聚糖的活性位点。钙离子与磷酸根在同一多孔吸附层内被不同位点分别捕获,二者无法在后续回用管路中重新结合形成磷酸钙垢,从而在反渗透产水外送前同步切断两种结垢离子,避免换热器及管路的沉积堵塞。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999160A_ABST
    Figure CN122999160A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of water treatment membrane materials, and specifically discloses a nano membrane for adsorbing trace residual ions, a preparation method and application thereof, the nano membrane comprising a support body and a porous adsorption layer loaded thereon, the porous adsorption layer being made of chitosan, polyethylene imine and cerium hydroxide nanoparticles by glutaraldehyde cross-linking and non-solvent induced phase separation, and having mesoporous channels formed after removal of silica nanoparticles as a hard template; the cerium hydroxide nanoparticles are converted in-situ from a cerium salt precursor in an alkaline coagulation bath and uniformly loaded in the porous adsorption layer. The application synchronously adsorbs trace phosphates and calcium ions through the combined action of cerium hydroxide nanoparticles and polyethylene imine at the end of reverse osmosis water production, prevents the two from recombining to form calcium phosphate scale in the reuse pipeline, prolongs the cleaning cycle of a heat exchanger and reduces the consumption of chemicals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water treatment membrane material technology, specifically relating to a nanomembrane for adsorbing trace residual ions, its preparation method, and its application. Background Technology

[0002] Acidic wastewater from phosphate chemical plants mainly originates from leachate from phosphogypsum stockpiles and wastewater from fluoride chemical plants. It is characterized by low pH, high fluoride and phosphorus content, and associated hardness ions such as calcium, magnesium, and silicon. The current mainstream treatment route is chemical neutralization followed by membrane recycling. First, a two-stage reaction precipitation process using lime and sodium aluminate removes most of the fluoride, phosphorus, and hardness. Then, deep desalination is achieved through ultrafiltration, nanofiltration, and reverse osmosis. The treated water is reused in the circulating cooling water loop or desalination plant. A 500m³ phosphate chemical plant in Anning, Yunnan Province... 3 The / h acidic water reuse unit adopts this route. The reverse osmosis unit is designed to have a water production rate of over 70%, with total phosphorus not exceeding 1 mg / L and calcium ion not exceeding 5 mg / L in the product water. In actual operation, the rejection rate of divalent ions by the reverse osmosis membrane is affected by the pH, temperature, and thickness of the fouling layer of the feed water. The total phosphorus in the product water often fluctuates between 0.8-3 mg / L, and the calcium ion concentration fluctuates between 8-20 mg / L. After this water is reused in the circulating cooling water loop, the calcium ion concentration increases with the concentration factor under the evaporation and concentration action of the cooling tower. Trace amounts of phosphate ions match this concentration and recombine in the heated zone of the heat exchanger tube bundle inner wall, forming a dense calcium phosphate scale layer. Within three months of operation, the unit experienced a temperature drop of over 15% in the heat exchanger, uneven water distribution in the packing, and nozzle blockage. The cleaning frequency increased from twice a year to once a quarter. Each chemical cleaning consumed a large amount of citric acid and corrosion inhibitors, accompanied by more than 48 hours of downtime.

[0003] Existing technologies primarily employ three end-point strategies to address trace calcium and phosphorus residues. The first involves continuously adding organophosphonic acid or polycarboxylic acid scale inhibitors and dispersants to the circulating water side. These inhibitors inhibit calcium phosphate crystallization by chelating calcium ions and mitigating lattice distortion. However, the dispersing ability of these scale inhibitors for trace ions decreases with increasing concentration ratios. Furthermore, organophosphonic agents themselves contain phosphorus, and continuous addition leads to a rebound in total phosphorus in the wastewater, causing secondary pollution and hindering the zero-discharge target. The second approach uses sodium-type cation exchange resins for deep hardening, exchanging calcium ions for sodium ions. However, sodium-type resins have a lower selectivity for calcium ions than sodium and potassium resins. When treating trace calcium, the exchange capacity utilization rate is less than 30%, the regeneration cycle is as short as 3-5 days, and regeneration consumes large amounts of sodium chloride and hydrochloric acid, generating high-salt regeneration wastewater and increasing the end-point evaporation load. The third type uses lanthanum-based hydrated oxides or zirconium-based MOF adsorbents specifically for phosphorus removal. These materials have a high affinity for phosphate ions and an equilibrium adsorption capacity of 30-50 mg / g, but they hardly adsorb calcium ions. After the produced water is sent out, the calcium ions remain in the water and can still combine with phosphate ions brought in by external makeup water or leaks to form scale when they enter the circulating water loop.

[0004] Current research also explores the use of chitosan or polyethyleneimine alone as adsorption materials for water treatment. Chitosan exhibits a certain chelating ability for heavy metals, but pure chitosan membranes easily swell or even dissolve in acidic or neutral water, lack sufficient mechanical strength, and have low selectivity for phosphate. Polyethyleneimine is rich in amino groups and can adsorb anions through electrostatic interactions; however, when used alone, it requires a cross-linking carrier for fixation, otherwise it is prone to loss. While simply blending and casting these two materials into a membrane can improve some performance, the lack of rigid mesoporous channels leads to high hydraulic resistance and slow mass transfer. Trace ions struggle to diffuse rapidly to the active sites within the membrane under low-concentration driving forces, limiting treatment efficiency. Furthermore, existing composite membranes primarily focus on the removal of single pollutants, with few reports on constructing dual-target adsorption sites for calcium and phosphorus within the same membrane, failing to address the scaling problem in reverse osmosis permeate reuse in phosphate chemical industries.

[0005] The common limitation of the aforementioned existing technologies is that they all target only a single ion for end-stage reduction, failing to simultaneously cut off both calcium and phosphate scaling ions before the reverse osmosis permeate is sent out. After the treated permeate enters the open circulating water loop, calcium and phosphate ions re-encounter under conditions of concentration, temperature increase, and pH fluctuations, rapidly reaching supersaturation in their solubility product. The risk of scaling is not eliminated, but merely delayed or transferred. There is an urgent need for a nanomembrane material at the end of the reverse osmosis permeate process capable of simultaneously adsorbing trace amounts of phosphate and calcium ions. This material should simultaneously reduce the concentrations of both ions to below the scaling tendency curve before reuse, preventing calcium phosphate deposition in subsequent pipelines and heat exchange equipment, extending cleaning cycles, and reducing reagent consumption.

[0006] Therefore, there is a need to design a nanofilm for adsorbing trace residual ions, as well as its preparation method and application. Summary of the Invention

[0007] To overcome the shortcomings of existing technologies, a nanofilm for adsorbing trace residual ions is provided, along with its preparation method and application.

[0008] To achieve the above objectives, the present invention provides the following technical solution: A nanofilm for adsorbing trace residual ions comprises a support and a porous adsorption layer loaded thereon. The porous adsorption layer is prepared by crosslinking chitosan, polyethyleneimine, and cerium hydroxide nanoparticles with glutaraldehyde and non-solvent-induced phase separation. The hydroxyl and amino groups on the chitosan chains have coordination adsorption for calcium ions, and the cerium hydroxide nanoparticles have coordination adsorption for phosphate ions and have mesoporous channels formed after the removal of silica nanoparticles as hard templates. The cerium hydroxide nanoparticles are uniformly loaded into the porous adsorption layer by in-situ conversion of cerium salt precursors in an alkaline coagulation bath.

[0009] Trace calcium and phosphorus residues at the end of reverse osmosis permeate are a prominent problem faced by phosphorus chemical recycling plants. Existing technologies mostly use scale inhibitors and dispersants or ion exchange resins, but these only target single ions and cannot simultaneously remove both calcium and phosphorus scaling ions. Although a simple blend of chitosan and polyethyleneimine can adsorb some ions, the lack of rigid mesoporous channels leads to high mass transfer resistance, and the selectivity for phosphate is insufficient.

[0010] This application introduces cerium hydroxide nanoparticles into a porous adsorption layer. Calcium ion adsorption sites are constructed using the hydroxyl and amino groups on the chitosan chains. Polyethyleneimine indirectly promotes the simultaneous removal of both ions through cross-linking enhancement and pore optimization. The surface of the cerium hydroxide nanoparticles is rich in hydroxyl groups, which can coordinate with phosphate ions, forming coordinate bonds between oxygen atoms and the cerium center, thus fixing trace amounts of phosphate ions to the pore wall surface of the porous adsorption layer. The hydroxyl and amino groups on the chitosan molecular chains can coordinate with calcium ions, fixing them to the pore wall surface of the porous adsorption layer. The physical retention of hydrated calcium ions by the membrane pores also removes calcium ions. After cross-linking with glutaraldehyde, polyethyleneimine and chitosan form a three-dimensional interpenetrating network, enhancing the mechanical strength of the porous adsorption layer and regulating the pore structure, allowing trace ions to rapidly diffuse to the active sites. Phosphate ions are fixed by cerium hydroxide nanoparticles, while calcium ions are fixed by hydroxyl and amino groups on chitosan. The two are captured at different sites within the same porous adsorption layer and cannot recombine to form calcium phosphate scale in subsequent reuse pipelines. Thus, the two scaling ions are simultaneously cut off before the reverse osmosis permeate is sent out.

[0011] However, self-supporting adsorption membranes are prone to damage during direct filling and backwashing, and their mechanical strength is insufficient to withstand the continuous shearing of water flow in the filtration section. Existing chitosan membranes are prone to swelling or even dissolving in acidic or neutral water, making it difficult to maintain long-term operation.

[0012] This application employs a support-supported structure, with the support selected from polyester nonwoven fabric, polyacrylonitrile ultrafiltration membrane, or porous ceramic sheets. The support provides a rigid substrate, upon which the porous adsorption layer is loaded to form a composite nanomembrane. The aldehyde groups of glutaraldehyde react with the amino groups of chitosan and polyethyleneimine to construct a three-dimensional cross-linked framework, ensuring the structural stability of the porous adsorption layer in acidic to neutral water and preventing swelling and breakage. The composite structure of the support and the cross-linked porous adsorption layer can be directly filled into the filtration section before the reverse osmosis permeate is sent out, maintaining structural integrity under operating pressure and facilitating maintenance and replacement.

[0013] The support is a polyester nonwoven fabric, a polyacrylonitrile ultrafiltration membrane, or a porous ceramic sheet.

[0014] A method for preparing a nanofilm for adsorbing trace residual ions, the method comprising the following steps: Step 1: Add cerium nitrate to an aqueous solution of chitosan in acetic acid, with a mass ratio of cerium ions to chitosan of 0.15:1-0.40:1. Stir at 15-30℃ for 4-6 hours to obtain a cerium-modified chitosan solution. Step 2: Add polyethyleneimine to the cerium-modified chitosan solution obtained in Step 1, wherein the mass ratio of polyethyleneimine to chitosan is 0.2:1-0.5:1, and stir for 1-2 hours to obtain a mixed solution of cerium-modified chitosan and polyethyleneimine. Step 3: Add silica nanoparticles to the mixed solution obtained in Step 2. The mass ratio of silica nanoparticles to chitosan is 0.2:1-0.6:1. After stirring and dispersing for 10-20 min, add glutaraldehyde aqueous solution. The ratio of the number of aldehyde groups in glutaraldehyde to the total number of amino groups in chitosan and polyethyleneimine is 0.5:1-1.5:1. After stirring for 15-30 min, degas to obtain the casting solution. The fourth step involves scraping the casting solution onto a support to form a liquid film with a thickness of 200-400 μm, immersing it in a coagulation bath, and washing it until neutral. During the coagulation process, cerium ions are converted in situ into cerium hydroxide nanoparticles and uniformly loaded into the porous adsorption layer. At the same time, silica nanoparticles are dissolved and removed to form mesoporous channels, resulting in a porous adsorption layer. The product obtained is a nanofilm used to adsorb trace residual ions.

[0015] In the first step, chitosan is dissolved in an aqueous solution with a volume fraction of 1%-3% acetic acid to prepare a chitosan solution with a mass percentage concentration of 3%-5%, wherein the degree of deacetylation of the chitosan is ≥85%.

[0016] In the second step, the molecular weight of the polyethyleneimine is 10,000-70,000.

[0017] In the third step, the particle size of the silica nanoparticles is 20-50 nm.

[0018] In the fourth step, the coagulation bath is composed of a sodium hydroxide aqueous solution and ethanol, with a sodium hydroxide concentration of 0.8-1.2 mol / L and an ethanol volume fraction of 25%-35%. This coagulation bath causes cerium ions to be converted into cerium hydroxide nanoparticles in situ, while simultaneously dissolving and removing silica nanoparticles to form mesoporous channels.

[0019] In the fourth step, the curing time is 30-60 minutes.

[0020] In existing technologies, the preparation of cerium-based adsorbent materials often employs co-precipitation or impregnation methods, which are disconnected from the film-forming process. As a result, nanoparticles tend to aggregate within the film or be lost with the water flow, making it difficult to disperse them uniformly.

[0021] This application employs a continuous four-step preparation method. First, cerium nitrate is coordinated with chitosan in an aqueous acetic acid solution, where cerium ions complex with the hydroxyl groups on the chitosan chains to obtain a cerium-modified chitosan solution. This coordination effect allows cerium ions to be uniformly anchored between chitosan segments at the molecular level, preventing localized aggregation during subsequent conversion. Next, polyethyleneimine is introduced to form a mixed solution, where the amino groups of polyethyleneimine interpenetrate and entangle with the chitosan segments, resulting in a cerium-modified chitosan and polyethyleneimine mixed solution. Subsequently, silica nanoparticles are dispersed and glutaraldehyde is added for cross-linking. The silica nanoparticles act as a hard template embedded in a three-dimensional cross-linked network, and the aldehyde groups of glutaraldehyde react with the amino groups of chitosan and polyethyleneimine to form a stable framework. Finally, the casting solution is coated onto a support and immersed in a coagulation bath. In an alkaline environment, cerium ions are converted in situ into cerium hydroxide nanoparticles, while the silica nanoparticles are dissolved and removed, forming mesoporous channels. Cerium hydroxide nanoparticles are uniformly loaded in the porous adsorption layer and do not dissolve with water flow. Mesoporous channels permeate the membrane, providing a low-resistance mass transfer path for trace ions.

[0022] Existing technologies have relatively crude control over the above preparation parameters. When the degree of deacetylation of chitosan is insufficient or the molecular weight of polyethyleneimine is mismatched, it is difficult to guarantee the coordination efficiency and crosslinking density, resulting in a decrease in adsorption capacity and mechanical strength.

[0023] In this application, chitosan is dissolved in an aqueous acetic acid solution with a degree of deacetylation ≥85%, ensuring a sufficient number of amino groups on the chitosan chains. This ensures that the coordination efficiency of cerium ions and subsequent glutaraldehyde crosslinking are both at reasonable levels. The mass ratio of polyethyleneimine to chitosan is 0.2:1-0.5:1, with a molecular weight of 10,000-70,000. Polyethyleneimine within this molecular weight range can interpenetrate and entangle with chitosan segments to form a mixed solution, which both strengthens the mechanical framework and provides high-density charge sites. Silica nanoparticles, acting as hard templates embedded in the crosslinking network, are dissolved in the coagulation bath to form mesoporous channels, balancing mass transfer rate and structural strength. The molar ratio of glutaraldehyde to the total amino groups of chitosan and polyethyleneimine is 0.5:1-1.5:1. This crosslinking density ensures the structural stability of the porous adsorbent layer in acidic to neutral water. The coagulation bath is a mixture of sodium hydroxide aqueous solution and ethanol. Ethanol slows down the phase separation rate, while sodium hydroxide provides an alkaline environment, enabling the casting solution to gel uniformly and simultaneously completing the in-situ conversion of cerium ions and the dissolution of silica. The curing time ensures sufficient phase separation and reasonable production efficiency.

[0024] An application of a nanomembrane for adsorbing trace residual ions, wherein the nanomembrane is used in the end-of-pipe treatment of reverse osmosis permeate. The nanomembrane is packed in the filtration section before the reverse osmosis permeate is sent out, treating reverse osmosis permeate with a total phosphorus concentration of 0.3-3 mg / L and a calcium ion concentration of 5-20 mg / L.

[0025] Existing end-of-pipe treatment methods often involve the continuous addition of chemical agents to the circulating water side, which fails to cut off scaling ions at the source and easily causes secondary pollution. This application incorporates a nanomembrane into the filtration section before the reverse osmosis permeate is sent out, directly treating the permeate before reuse. This nanomembrane has the ability to simultaneously remove total phosphorus concentrations of 0.3-3 mg / L and calcium ion concentrations of 5-20 mg / L from reverse osmosis permeate, operates at low pressure, does not introduce external chemical agents, and causes no secondary pollution to the reclaimed water. The mesoporous channels in the porous adsorption layer allow water to pass through in a laminar flow state, prolonging the contact time between trace ions and active sites. The cerium hydroxide nanoparticles and protonated amino groups work together to fix calcium and phosphorus ions at different sites on the pore walls. Scaling ions before the permeate is sent out are simultaneously cut off, thereby reducing the risk of scaling in the circulating water loop. It can be directly embedded in existing reuse pipelines, extending the heat exchanger cleaning cycle and reducing chemical consumption.

[0026] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. The porous adsorption layer of this application contains cerium hydroxide nanoparticles, which can coordinate with phosphate ions, fixing trace amounts of phosphate ions to the pore wall surface of the porous adsorption layer. The hydroxyl and amino groups on the chitosan chains can coordinate with calcium ions, fixing the calcium ions to the pore wall surface of the porous adsorption layer. Polyethyleneimine and chitosan are cross-linked with glutaraldehyde to form a three-dimensional interpenetrating network, enhancing the mechanical strength of the porous adsorption layer and regulating the pore structure, allowing trace calcium ions to rapidly diffuse to the active sites of chitosan. Calcium ions and phosphate ions are captured separately at different sites within the same porous adsorption layer, preventing them from recombining to form calcium phosphate scale in subsequent reuse pipelines. This simultaneously cuts off the two scaling ions before the reverse osmosis permeate is sent out, avoiding deposition and blockage in heat exchangers and pipelines.

[0027] 2. This application uses cerium nitrate as a precursor, which is converted in situ into cerium hydroxide nanoparticles in an alkaline coagulation bath. This conversion process occurs simultaneously with the gelation of the membrane, ensuring that the nanoparticles are uniformly loaded in the porous adsorption layer, thus simplifying the preparation process. Glutaraldehyde reacts with the amino groups of chitosan and polyethyleneimine to form a cross-linked network, endowing the porous adsorption layer with good mechanical strength and water resistance, allowing it to maintain structural stability in acidic to neutral reverse osmosis permeate water and avoiding performance degradation caused by swelling and breakage.

[0028] 3. This application uses silica nanoparticles as a hard template, which are dissolved and removed in an alkaline coagulation bath to form mesoporous channels. These channels penetrate the porous adsorption layer, providing a low-resistance mass transfer path for water flow. Trace amounts of phosphate and calcium ions can rapidly diffuse to the active sites under low-concentration driving forces. The composite structure of chitosan and polyethyleneimine combines mechanical support and charge adsorption functions, enabling the porous adsorption layer to maintain high porosity while possessing sufficient structural integrity.

[0029] 4. The preparation method of this application employs solvent-free phase separation, with readily available raw materials, facilitating industrial production. The resulting nanomembrane can be directly packed into the filtration section before the reverse osmosis permeate is sent out, without requiring significant modifications to existing pipelines. It operates at low pressure, poses no risk of secondary pollution to the recycled water, and is suitable for deep purification of trace ions at the end of reverse osmosis permeate. Attached Figure Description

[0030] Figure 1 This figure shows the total phosphorus removal rate and calcium ion removal rate of each embodiment and comparative example to compare the removal rates of reverse osmosis permeate at the end of the treatment process.

[0031] Figure 2 To compare the concentrations of permeate after end-of-pipe treatment in reverse osmosis, this figure shows the total phosphorus concentration and calcium ion concentration of permeate in each embodiment and comparative example.

[0032] Figure 3 To illustrate the membrane structure and mechanical properties, the figure is divided into four parts: A represents tensile strength, B represents the average pore size of the mesopores, C represents the pure water flux, and D represents the particle size of cerium hydroxide nanoparticles.

[0033] Figure 4 This is a process flow diagram of a method for preparing a nanofilm for adsorbing trace residual ions. Detailed Implementation

[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0035] In the specific embodiments of this application, the sources of various main raw materials are briefly described as follows: Chitosan was purchased from Wuhan Xianghe Shunda Biotechnology Co., Ltd., with a degree of deacetylation of ≥95% and CAS number 9012-76-4. Acetic acid was purchased from Jiangsu Suopu Chemical Co., Ltd., CAS No. 64-19-7; Cerium nitrate was purchased from Condis Chemical (Hubei) Co., Ltd., CAS No. 10294-41-4, product name: cerium nitrate hexahydrate, purity specification: 99%.

[0036] Polyethyleneimine was purchased from Wuhan Qianglong Chemical New Materials Co., Ltd., CAS No. 9002-98-6, model QL-1001-C-3, weight average molecular weight (Mw): 17000~20000.

[0037] Silica nanoparticles were purchased from Shanghai Naio Nanotechnology Co., Ltd., with a particle size of 20-50nm.

[0038] The glutaraldehyde aqueous solution was purchased from Shandong Ruigang Chemical Co., Ltd.

[0039] The polyester nonwoven fabric was purchased from Hangzhou Nuobang Nonwoven Co., Ltd.

[0040] The polyacrylonitrile ultrafiltration membrane was purchased from Tianjin Membrane Technology Group Co., Ltd.

[0041] The porous ceramic sheet was purchased from Shandong Industrial Ceramics Research and Design Institute Co., Ltd.

[0042] The technical solution of this application is as follows: A nanofilm for adsorbing trace residual ions comprises a support and a porous adsorption layer loaded thereon. The porous adsorption layer is prepared by crosslinking chitosan, polyethyleneimine, and cerium hydroxide nanoparticles with glutaraldehyde and non-solvent-induced phase separation. The hydroxyl and amino groups on the chitosan chains have coordination adsorption for calcium ions, and the cerium hydroxide nanoparticles have coordination adsorption for phosphate ions and have mesoporous channels formed after the removal of silica nanoparticles as hard templates. The cerium hydroxide nanoparticles are uniformly loaded into the porous adsorption layer by in-situ conversion of cerium salt precursors in an alkaline coagulation bath.

[0043] The support is a polyester nonwoven fabric, a polyacrylonitrile ultrafiltration membrane, or a porous ceramic sheet.

[0044] A method for preparing a nanofilm for adsorbing trace residual ions, such as... Figure 4 As shown, the preparation method includes the following steps: Step 1: Add cerium nitrate to an aqueous solution of chitosan in acetic acid, with a mass ratio of cerium ions to chitosan of 0.15:1-0.40:1. Stir at 15-30℃ for 4-6 hours to obtain a cerium-modified chitosan solution. Step 2: Add polyethyleneimine to the cerium-modified chitosan solution obtained in Step 1, wherein the mass ratio of polyethyleneimine to chitosan is 0.2:1-0.5:1, and stir for 1-2 hours to obtain a mixed solution of cerium-modified chitosan and polyethyleneimine. Step 3: Add silica nanoparticles to the mixed solution obtained in Step 2. The mass ratio of silica nanoparticles to chitosan is 0.2:1-0.6:1. After stirring and dispersing for 10-20 min, add glutaraldehyde aqueous solution. The ratio of the number of aldehyde groups in glutaraldehyde to the total number of amino groups in chitosan and polyethyleneimine is 0.5:1-1.5:1. After stirring for 15-30 min, degas to obtain the casting solution. The fourth step involves scraping the casting solution onto a support to form a liquid film with a thickness of 200-400 μm, immersing it in a coagulation bath, and washing it until neutral. During the coagulation process, cerium ions are converted in situ into cerium hydroxide nanoparticles and uniformly loaded into the porous adsorption layer. At the same time, silica nanoparticles are dissolved and removed to form mesoporous channels, resulting in a porous adsorption layer. The product obtained is a nanofilm used to adsorb trace residual ions.

[0045] In the first step, chitosan is dissolved in an aqueous solution with a volume fraction of 1%-3% acetic acid to prepare a chitosan solution with a mass percentage concentration of 3%-5%, wherein the degree of deacetylation of the chitosan is ≥85%.

[0046] In the second step, the molecular weight of the polyethyleneimine is 10,000-70,000.

[0047] In the third step, the particle size of the silica nanoparticles is 20-50 nm.

[0048] In the fourth step, the coagulation bath is composed of a sodium hydroxide aqueous solution and ethanol, with a sodium hydroxide concentration of 0.8-1.2 mol / L and an ethanol volume fraction of 25%-35%. This coagulation bath causes cerium ions to be converted into cerium hydroxide nanoparticles in situ, while simultaneously dissolving and removing silica nanoparticles to form mesoporous channels.

[0049] In the fourth step, the curing time is 30-60 minutes.

[0050] An application of a nanomembrane for adsorbing trace residual ions, the nanomembrane being used in the end-of-pipe treatment of reverse osmosis permeate.

[0051] The nanomembrane is packed into the filtration section before the reverse osmosis permeate is sent out, and it treats reverse osmosis permeate with a total phosphorus concentration of 0.3-3 mg / L and a calcium ion concentration of 5-20 mg / L.

[0052] The present invention will be described in detail below through examples and comparative examples, but the scope of protection of the present invention is not limited to these examples. Unless otherwise specified, the chemical reagents and raw materials used in the following examples and comparative examples are all conventional commercially available products.

[0053] Example 1

[0054] Chitosan was dissolved in a 2% (v / v) aqueous solution of acetic acid to prepare a 3% (w / w) chitosan solution. Cerium nitrate was added to this chitosan solution, with a cerium ion to chitosan mass ratio of 0.40:1. The mixture was stirred at 23°C for 4 hours, during which cerium ions coordinated with the hydroxyl groups of chitosan to obtain a cerium-modified chitosan solution.

[0055] Polyethyleneimine was added to the cerium-modified chitosan solution at a mass ratio of 0.5:1. After stirring for 1.5 h, the amino groups of polyethyleneimine interpenetrated and entangled with the chitosan segments, resulting in a mixed solution of cerium-modified chitosan and polyethyleneimine.

[0056] Silica nanoparticles were added to the mixed solution, with a mass ratio of silica nanoparticles to chitosan of 0.2:1. After stirring and dispersing for 20 min, glutaraldehyde aqueous solution was added, with a ratio of the number of aldehyde moles in glutaraldehyde to the total number of amino moles in chitosan and polyethyleneimine of 1.0:1. After stirring for 15 min, the solution was degassed to obtain the casting solution.

[0057] The casting solution was scraped onto a polyester nonwoven fabric to form a liquid film with a thickness of 400 μm. The film was then immersed in a coagulation bath composed of sodium hydroxide aqueous solution and ethanol, with a sodium hydroxide concentration of 1.0 mol / L and an ethanol volume fraction of 25%. The film was cured for 60 min. The cured film was then immersed in a 2.0 mol / L sodium hydroxide solution and eluted by shaking at 70 °C for 18 h. The eluted film was then heat-treated at 60 °C for 3 h and washed until neutral to completely dissolve the silica nanoparticles. During the curing process, cerium ions were converted in situ into cerium hydroxide nanoparticles and uniformly loaded into the porous adsorption layer. At the same time, the silica nanoparticles were dissolved and removed to form mesoporous channels, resulting in a porous adsorption layer.

[0058] Example 2

[0059] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: Chitosan was dissolved in a 3% (v / v) aqueous solution of acetic acid to prepare a 4% (w / w) chitosan solution. Cerium nitrate was added to this chitosan solution at a cerium ion to chitosan mass ratio of 0.15:1. The mixture was stirred at 30°C for 5 hours, during which cerium ions coordinated with the hydroxyl groups of chitosan to obtain a cerium-modified chitosan solution.

[0060] Polyethyleneimine was added to the cerium-modified chitosan solution at a mass ratio of 0.2:1. After stirring for 2 hours, the amino groups of polyethyleneimine interpenetrated and entangled with the chitosan segments, resulting in a mixed solution of cerium-modified chitosan and polyethyleneimine.

[0061] Silica nanoparticles were added to the mixed solution, with a mass ratio of silica nanoparticles to chitosan of 0.4:1. After stirring and dispersing for 10 min, glutaraldehyde aqueous solution was added, with a ratio of the number of aldehyde moles in glutaraldehyde to the total number of amino moles in chitosan and polyethyleneimine of 1.5:1. After stirring for 23 min, the solution was degassed to obtain the casting solution.

[0062] The casting solution was scraped onto a polyacrylonitrile ultrafiltration membrane to form a liquid film with a thickness of 200 μm. The film was then immersed in a coagulation bath composed of sodium hydroxide aqueous solution and ethanol, with a sodium hydroxide concentration of 1.2 mol / L and an ethanol volume fraction of 30%. The film was cured for 30 min and washed until neutral. During the curing process, cerium ions were converted in situ into cerium hydroxide nanoparticles and uniformly loaded into the porous adsorption layer. At the same time, silica nanoparticles were dissolved and removed to form mesoporous channels, thus obtaining the porous adsorption layer.

[0063] Example 3

[0064] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: Chitosan was dissolved in a 1% (v / v) aqueous solution of acetic acid to prepare a 5% (w / w) chitosan solution. Cerium nitrate was added to this chitosan solution, with a cerium ion to chitosan mass ratio of 0.28:1. The mixture was stirred at 15°C for 6 hours, during which cerium ions coordinated with the hydroxyl groups of chitosan to obtain a cerium-modified chitosan solution.

[0065] Polyethyleneimine was added to the cerium-modified chitosan solution at a mass ratio of 0.35:1. After stirring for 1 hour, the amino groups of polyethyleneimine interpenetrated and entangled with the chitosan segments, resulting in a mixed solution of cerium-modified chitosan and polyethyleneimine.

[0066] Silica nanoparticles were added to the mixed solution, with a mass ratio of silica nanoparticles to chitosan of 0.6:1. After stirring and dispersing for 15 min, glutaraldehyde aqueous solution was added, with a ratio of the number of aldehyde moles in glutaraldehyde to the total number of amino moles in chitosan and polyethyleneimine of 0.5:1. After stirring for 30 min, the solution was degassed to obtain the casting solution.

[0067] The casting solution was scraped onto a porous ceramic sheet to form a liquid film with a thickness of 300 μm. The film was then immersed in a coagulation bath composed of sodium hydroxide aqueous solution and ethanol, with a sodium hydroxide concentration of 0.8 mol / L and an ethanol volume fraction of 35%. The film was cured for 45 min and washed until neutral. During the curing process, cerium ions were converted in situ into cerium hydroxide nanoparticles and uniformly loaded into the porous adsorption layer. At the same time, silica nanoparticles were dissolved and removed to form mesoporous channels, thus obtaining the porous adsorption layer.

[0068] Example 4

[0069] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: Chitosan was dissolved in a 2% (v / v) aqueous solution of acetic acid to prepare a 4% (w / w) chitosan solution. Cerium nitrate was added to this chitosan solution at a cerium ion to chitosan mass ratio of 0.30:1. The mixture was stirred at 25°C for 5 hours, during which cerium ions coordinated with the hydroxyl groups of chitosan to obtain a cerium-modified chitosan solution.

[0070] Polyethyleneimine was added to the cerium-modified chitosan solution at a mass ratio of 0.35:1. After stirring for 1.5 h, the amino groups of polyethyleneimine interpenetrated and entangled with the chitosan segments, resulting in a mixed solution of cerium-modified chitosan and polyethyleneimine.

[0071] Silica nanoparticles were added to the mixed solution, with a mass ratio of silica nanoparticles to chitosan of 0.4:1. After stirring and dispersing for 15 min, glutaraldehyde aqueous solution was added, with a ratio of the number of aldehyde moles in glutaraldehyde to the total number of amino moles in chitosan and polyethyleneimine of 1.0:1. After stirring for 20 min, the solution was degassed to obtain the casting solution.

[0072] The casting solution was scraped onto a polyester nonwoven fabric to form a liquid film with a thickness of 300 μm. The film was then immersed in a coagulation bath composed of sodium hydroxide aqueous solution and ethanol, with a sodium hydroxide concentration of 1.0 mol / L and an ethanol volume fraction of 30%. The film was cured for 45 min and washed until neutral. During the curing process, cerium ions were converted in situ into cerium hydroxide nanoparticles and uniformly loaded into the porous adsorption layer. At the same time, silica nanoparticles were dissolved and removed to form mesoporous channels, thus obtaining the porous adsorption layer.

[0073] Comparative Example 1 The preparation methods of Comparative Example 1 and Example 1 are basically the same, except that cerium nitrate is not added in the first step, that is, cerium ion coordination modification is not performed. Other steps and parameters are consistent with those of Example 1.

[0074] Comparative Example 2 The preparation methods of Comparative Example 2 and Example 2 are basically the same, except that polyethyleneimine is not added in the second step, that is, polyethyleneimine crosslinking reinforcement is not performed. Other steps and parameters are consistent with those of Example 2.

[0075] Comparative Example 3 The preparation methods of Comparative Example 3 and Example 3 are basically the same, except that the ratio of the number of aldehyde groups in glutaraldehyde to the total number of amino groups in chitosan and polyethyleneimine in the third step is 0.2:1. Other steps and parameters are consistent with those of Example 3.

[0076] Comparative Example 4 The preparation methods of Comparative Example 4 and Example 4 are basically the same, except that silica nanoparticles are not added in the third step, that is, silica nanoparticles are not used as hard templates. Other steps and parameters are consistent with those of Example 4.

[0077] Performance Test Results and Analysis The nanomembranes obtained from the four examples and four comparative examples were respectively packed into the filtration section before the reverse osmosis permeate was sent out, treating reverse osmosis permeate with a total phosphorus concentration of 1 mg / L and a calcium ion concentration of 10 mg / L. The operating pressure was 0.1 MPa and the hydraulic retention time was 20 min. The permeate quality, membrane structure, and mechanical properties were measured. The specific test results are as follows: Figure 1-3 As shown.

[0078] The testing methods were as follows: Inductively coupled plasma atomic emission spectrometry (ICP-AES) was used to determine the total phosphorus and calcium ion concentrations in the product water; scanning electron microscopy was used to observe the surface morphology of the porous adsorption layer; mercury porosimetry was used to determine the average pore size and pore volume of the mesopores; Fourier transform infrared spectroscopy was used to analyze the functional group changes in the porous adsorption layer; X-ray diffraction was used to analyze the crystal form of cerium hydroxide nanoparticles; transmission electron microscopy was used to determine the particle size and distribution of cerium hydroxide nanoparticles; a universal testing machine was used to determine the tensile strength of the membrane; and a cross-flow filtration device was used to determine the pure water flux at an operating pressure of 0.1 MPa.

[0079] from Figure 1 , Figure 2 As can be seen, the total phosphorus removal rate in Examples 1 to 4 is all above 90%, with total phosphorus in the produced water below 0.1 mg / L, and the calcium ion removal rate is all above 90%, with calcium ion concentration in the produced water not exceeding 1 mg / L. This is due to the coordination effect of cerium hydroxide nanoparticles on phosphate ions in the porous adsorption layer. The surface of cerium hydroxide nanoparticles is rich in hydroxyl groups, which coordinate and complex with phosphate ions, forming stable bonds between oxygen atoms and cerium centers, thus fixing trace amounts of phosphate ions to the pore wall surface. The hydroxyl and amino groups on the chitosan chains coordinate and complex with calcium ions, and the cross-linking of polyethyleneimine and chitosan forms a dense network, which prolongs the residence time of calcium ions in the membrane and makes the coordination adsorption more complete. Calcium ions and phosphate ions are fixed separately at different sites in the same porous adsorption layer and cannot recombine to form calcium phosphate scale in the subsequent reuse pipeline.

[0080] Comparative Example 1, lacking cerium ion coordination modification, contained no cerium hydroxide nanoparticles in its porous adsorption layer. Chitosan itself exhibited low selectivity for phosphate, resulting in a total phosphorus removal rate of only 18%. Comparative Example 2, while containing cerium hydroxide nanoparticles, lacked polyethyleneimine, leading to a sparse cross-linking network. After the chitosan segments swelled in the permeate, the contact efficiency between hydroxyl and amino groups and calcium ions decreased. Furthermore, the loose membrane pore structure shortened the hydraulic retention time, reducing the calcium ion removal rate to 15%. Comparative Example 3 suffered from insufficient glutaraldehyde cross-linking, resulting in partial swelling of the porous adsorption layer in the permeate and deformation of the mesoporous channels. This reduced the contact efficiency between cerium hydroxide nanoparticles and phosphate, resulting in a total phosphorus removal rate of 70%. Simultaneously, partial loss of polyethyleneimine led to a calcium ion removal rate of 68%. Comparative Example 4 lacked silica nanoparticles as a hard template, resulting in an average mesopore diameter of only 2 nm. Trace amounts of phosphate and calcium ions struggled to diffuse to deeper active sites within the membrane, resulting in a total phosphorus removal rate of 60% and a calcium ion removal rate of 58%.

[0081] from Figure 3 As can be seen from the data, the tensile strength of Examples 1 to 4 is all higher than 12 MPa, and the pure water flux is higher than 42 L / (m²). 2 ·h). Glutaraldehyde reacts with the amino groups of chitosan and polyethyleneimine to form a three-dimensional cross-linked framework, endowing the porous adsorption layer with good mechanical strength and water resistance. Silica nanoparticles, acting as a hard template, form mesoporous channels after dissolution, reducing hydraulic resistance and allowing trace ions to diffuse rapidly to the active sites. In Comparative Example 3, the glutaraldehyde dosage was too low, resulting in a sparse cross-linked network and a tensile strength of only 3 MPa. The membrane easily swelled and deformed in the permeate, and the pore distortion led to a flux reduction to 28 L / (m²·h). Comparative Example 4 lacked a hard template, resulting in a scarcity of mesopores, high mass transfer resistance, and a flux reduction to 18 L / (m²·h). The tensile strength and flux of Comparative Examples 1 and 2 were close to those of the examples, but their adsorption performance was poor. This indicates that the synergistic presence of hydroxyl and amino groups on chitosan and cerium hydroxide nanoparticles is key to the simultaneous removal of calcium and phosphorus. Polyethyleneimine indirectly enhances this synergistic effect by optimizing the cross-linked network and pore structure.

[0082] The cerium hydroxide nanoparticles in Examples 1 to 4 had a particle size of 6-12 nm and were uniformly dispersed in a porous adsorption layer. This was due to the prior metal ion coordination between cerium nitrate and chitosan in an aqueous acetic acid solution, where cerium ions were anchored to chitosan segments at the molecular level, preventing aggregation during subsequent alkaline coagulation. Comparative Example 2 lacked polyethyleneimine, resulting in a lower viscosity of the mixed solution, poor casting solution stability, and affected particle dispersion. Comparative Example 3 had insufficient cross-linking, a loose network, and particles were prone to local migration. Comparative Example 4 lacked mesopores, with particles encapsulated in a dense network, reducing accessibility. These results indicate that the three steps of metal ion coordination, enhanced polyethyleneimine cross-linking, and silica porosification work together to achieve uniform nanoscale dispersion of cerium hydroxide nanoparticles with high ion accessibility.

[0083] This invention utilizes the combined action of cerium hydroxide nanoparticles and polyethyleneimine at the end of the reverse osmosis permeate flow to simultaneously adsorb trace amounts of phosphate and calcium ions, preventing them from recombining in the reuse pipeline to form calcium phosphate scale, thus extending the heat exchanger cleaning cycle and reducing reagent consumption.

[0084] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A nanofilm for adsorbing trace residual ions, characterized in that, The nanofilm comprises a support and a porous adsorption layer loaded thereon. The porous adsorption layer is made by crosslinking chitosan, polyethyleneimine, and cerium hydroxide nanoparticles with glutaraldehyde and non-solvent-induced phase separation. The hydroxyl and amino groups on the chitosan chains have coordination adsorption for calcium ions, and the cerium hydroxide nanoparticles have coordination adsorption for phosphate ions and have mesoporous channels formed after the removal of silica nanoparticles as hard templates. The cerium hydroxide nanoparticles are uniformly loaded in the porous adsorption layer by in-situ transformation of cerium salt precursors in an alkaline coagulation bath.

2. The nanofilm for adsorbing trace residual ions according to claim 1, characterized in that, The support is a polyester nonwoven fabric, a polyacrylonitrile ultrafiltration membrane, or a porous ceramic sheet.

3. A method for preparing a nanofilm for adsorbing trace residual ions as described in claim 1 or 2, characterized in that, The preparation method includes the following steps: Step 1: Add cerium nitrate to an aqueous solution of chitosan in acetic acid, with a mass ratio of cerium ions to chitosan of 0.15:1-0.40:

1. Stir at 15-30℃ for 4-6 hours to obtain a cerium-modified chitosan solution. Step 2: Add polyethyleneimine to the cerium-modified chitosan solution obtained in Step 1, wherein the mass ratio of polyethyleneimine to chitosan is 0.2:1-0.5:1, and stir for 1-2 hours to obtain a mixed solution of cerium-modified chitosan and polyethyleneimine. Step 3: Add silica nanoparticles to the mixed solution obtained in Step 2. The mass ratio of silica nanoparticles to chitosan is 0.2:1-0.6:

1. After stirring and dispersing for 10-20 min, add glutaraldehyde aqueous solution. The ratio of the number of aldehyde groups in glutaraldehyde to the total number of amino groups in chitosan and polyethyleneimine is 0.5:1-1.5:

1. After stirring for 15-30 min, degas to obtain the casting solution. The fourth step involves scraping the casting solution onto a support to form a liquid film with a thickness of 200-400 μm, immersing it in a coagulation bath, and washing it until neutral. During the coagulation process, cerium ions are converted in situ into cerium hydroxide nanoparticles and uniformly loaded into the porous adsorption layer. At the same time, silica nanoparticles are dissolved and removed to form mesoporous channels, resulting in a porous adsorption layer. The product obtained is a nanofilm used to adsorb trace residual ions.

4. The method for preparing a nanofilm for adsorbing trace residual ions according to claim 3, characterized in that, In the first step, chitosan is dissolved in an aqueous solution with a volume fraction of 1%-3% acetic acid to prepare a chitosan solution with a mass percentage concentration of 3%-5%, wherein the degree of deacetylation of the chitosan is ≥85%.

5. The method for preparing a nanofilm for adsorbing trace residual ions according to claim 3, characterized in that, In the second step, the molecular weight of the polyethyleneimine is 10,000-70,000.

6. The method for preparing a nanofilm for adsorbing trace residual ions according to claim 3, characterized in that, In the third step, the particle size of the silica nanoparticles is 20-50 nm.

7. The method for preparing a nanofilm for adsorbing trace residual ions according to claim 3, characterized in that, In the fourth step, the coagulation bath is composed of a sodium hydroxide aqueous solution and ethanol, with a sodium hydroxide concentration of 0.8-1.2 mol / L and an ethanol volume fraction of 25%-35%. This coagulation bath causes cerium ions to be converted into cerium hydroxide nanoparticles in situ, while simultaneously dissolving and removing silica nanoparticles to form mesoporous channels.

8. The method for preparing a nanofilm for adsorbing trace residual ions according to claim 3, characterized in that, In the fourth step, the curing time is 30-60 minutes.

9. An application of a nanofilm for adsorbing trace residual ions as described in claim 1 or 2, characterized in that, The nanomembrane is used for the end-of-pipe treatment of reverse osmosis permeate.

10. The application of the nanofilm for adsorbing trace residual ions according to claim 9, characterized in that, The nanomembrane is packed into the filtration section before the reverse osmosis permeate is sent out, and it treats reverse osmosis permeate with a total phosphorus concentration of 0.3-3 mg / L and a calcium ion concentration of 5-20 mg / L.